Analisis Nilai Saksi dalam Proses Pembuktian Menurut Hukum Acara Perdata - Fauziah Lubis; Najwa Ramadhani Lubis; Saidatul Umniyyah; Junita Lubis; Muhammad Fauzan; Muhammad Dzaky Al Muttaqy (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
In civil procedural law, witnesses play a crucial role as evidence to clarify disputed facts, especially when written evidence is insufficient. According to Article 164 of HIR and Article 1865 of the Civil Code, witness testimony must be given under oath to gain legal legitimacy. The principle of "Unus Testis Nullus Testis" states that the testimony of a single witness must be supported by other evidence to have probative value. The procedures involve a witness list, scheduling of hearings, summoning, taking of the oath, and examination of testimony. Judges evaluate testimony based on its relevance, consistency, and connection with other evidence. The strength of witness testimony lies in direct experience, objectivity, and consistency. However, weaknesses such as testimonium de auditu (hearsay evidence), personal bias, and memory limitations can affect its validity. Under the principle of "vrije bewijsleer" (free evaluation of evidence), judges assess testimony independently within a relevant context. Although supplementary, witness testimony is often crucial in supporting or rejecting the claims of disputing parties, aiming to reach a fair judgment based on credible facts.